The examination of the effect of caffeine supplementation in professional soccer players - S. Karabağ; Z. Taş (Physical Education of Students)
Purpose: In this study, the effects of caffeine supplementation in professional soccer players on the Hoff and sprint tests were examined. Material: 11 professional soccer players participated in this study in line with this purpose (Xage=20.636). The Hoff and sprint tests were applied 3 times at 1 week intervals. In each of these practices, caffeine added water was performed on the participants in the first week, and placebo was performed in the second week. In the third week, the participants were tested without any additional supplement. This practice lasted 3 weeks. Caffeine supplementation was given to each participant with the amount of 6 mg / kg in 200 ml water 1 hour before the tests, and placebo supplementation in 200 ml water was given 1 hour before the tests. The soccer players did the hoff test and sprint test respectively after 20 minutes of warming period. Results: Following Wilcoxon signed-ranks analysis, it was found that caffeine supplementation and placebo applications significantly increased the hoff test averages (p <0.05), while sprint test averages were reduced significantly in statistical terms (p <0.05). Conclusions: As a conclusion, we can state that caffeine application significantly increased the hoff test averages in comparison to placebo (p <0.05), and that it caused sprint test averages to decrease significantly in statistical terms (p <0.05).